Studi Empiris tentang Pengaruh Kepemimpinan Karismatik, Lingkungan Kerja, dan Kompensasi terhadap Loyalitas Karyawan di Yayasan Darut Taqwa - M. Afifulloh Yusuf; Nur Rohmad Nuzil (CV. Satria Jaya, 2024)
This study aims to determine the influence of charismatic leadership, work environment, and compensation on employee loyalty. The approach used in this study is quantitative with the type of causal associative research. The data collection technique was carried out through the distribution of questionnaires to 80 respondents who were selected using the purposive sampling method, which is the selection of samples based on certain criteria relevant to the purpose of the research. Data analysis was carried out using multiple linear regression to test the simultaneous or partial influence of independent variables on dependent variables. The results of this research are expected to contribute to the development of human resource management strategies, especially in increasing employee loyalty through leadership, a conducive work environment, and an effective compensation system